Optimal traffic calming: A mixed-integer bi-level programming model for locating sidewalks and crosswalks in a multimodal transportation network to maximize pedestrians’ safety and network usability - Rashidi, Eghbal; Parsafard, Mohsen; Medal, Hugh; Li, Xiaopeng (Transportation research. Part E, Logistics and transportation review, 2016)
•We study how to allocate resources for constructing sidewalks and crosswalks in order to calm traffic.•A mixed integer nonlinear programming model is presented for optimally locating sidewalks and crosswalks.•A customized greedy heuristic and a simulated annealing algorithm are developed for the problem.•Sidewalks and crosswalks not only increase pedestrian safety but also reduce transportation cost. We study the effect that installing sidewalks and crosswalks, as traffic calming facilities, has on the safety and usability of a transportation network with automobile, public transit and walking as modes of transportation. A mathematical programming model is proposed for this problem whose objective is to minimize the safety hazard for pedestrians and the total transportation cost of the network. We utilize a customized greedy heuristic and a simulated annealing algorithm for solving the problem. The computational results indicate that installing sidewalks and crosswalks at proper locations can reduce the overall transportation cost and improve pedestrians’ safety.